Konkurrenz belebt das Geschäft? Das Filialgeschäft der Commerzbank in den 1920er- und 1930er- Jahren zwischen Expansion und Konkurrenzdruck - Falk Liedtke (IBF - Institut für Bank- und Finanzgeschichte e.V., 2024)
In the 1910s and 1920s, the major Berlin private banks created extensive branch networks. Among them the Commerzbank stood out in particular, building up the second-largest branch network by the mid-1920s. However, the expansion was plagued by problems from the outset. Until the 1930s, Commerzbank was only moderately successful in implementing its business strategies in the new branches. The organization of the customer lending business in particular was burdened by arbitrary and often risky business decisions by the branches, which ultimately contributed significantly to the bank's liquidity problems during the banking crisis of 1931. The risky branch business was directly linked to the aggressive expansion strategies of the major Berlin banks, whose rapidly growing number of branches competed with each other in an increasingly crowded market in the 1920s. An examination of the surviving sources from Commerzbank's branch business reveals an instrumentalization of the customer lending business, whereby an increasing willingness to take risks in lending was used as a tool in competition with a growing number of rival banks.
Keywords: N24; D04; G21; 330; Bank History; Credit; Competition; Financial Crisis History; History ofFinancial Institutions; Lending; Market Structure